2007
DOI: 10.1002/pd.1771
|View full text |Cite
|
Sign up to set email alerts
|

Embryology of neural tube defects: information provided by associated malformations

Abstract: NDT are more extensive congenital damages that would suggest the restrictive terminology. That prompts to assess cautiously prenatal diagnosis of NTD, and to get detailed pathological examination after termination of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…To analyze the correlation between PARD3 polymorphisms and NTD phenotypes, fetuses with the 2 most common NTD phenotypes (anencephaly and spina bifida) were collected. The classification methods used in this study were based on those devised by Cabaret et al 26 At last, 224 cases with NTDs and 253 nonmalformed controls were collected. Of the 224 NTD-affected fetuses, there were 149 cases with anencephaly, and 75 cases with spina bifida.…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the correlation between PARD3 polymorphisms and NTD phenotypes, fetuses with the 2 most common NTD phenotypes (anencephaly and spina bifida) were collected. The classification methods used in this study were based on those devised by Cabaret et al 26 At last, 224 cases with NTDs and 253 nonmalformed controls were collected. Of the 224 NTD-affected fetuses, there were 149 cases with anencephaly, and 75 cases with spina bifida.…”
Section: Resultsmentioning
confidence: 99%
“…Eighty‐six fetuses with spina bifida, 64 with anencephalus, 15 with encephalocele, and 152 control subjects were selected for genotyping (Table ). The classification methods were based on those devised by Cabaret et al (). Control fetuses were aborted for nonmedical reasons and were also obtained from Shanxi Province and selected for methylation analysis and genotyping according to sex and gestation period.…”
Section: Methodsmentioning
confidence: 99%
“…So we analyzed the association of the ITPK1 polymorphisms with NTD phenotypes (anencephaly, spina bifida). The subtypes were based on those devised by Cabaret et al [20]. The research found that in the spina bifida group, individuals with the heterozygosis genotype were at a significantly increased risk for NTDs, compared with the wide type genotype (Table 5).…”
Section: Resultsmentioning
confidence: 99%